Ownership structure and loan quality of deposit money banks in Nigeria - Daniya Adeiza Abdulazeez (Universitas Islam Negeri (UIN) Walisongo Semarang, 2021)
Purpose - This study examined the effect of Ownership Structure (Management Shareholding and Ownership Concentration) on the loan quality (LDR) of banks in Nigeria for a period of 10 years (2008-2017). The study utilized data extracted from the annual reports of the fourteen (14) studied banks.Method - Robustness tests were carried out to determine: the existence or otherwise of multi-collinearity, fitness of the model and appropriate regression analysis for the study. Descriptive statistics, correlation and Fixed Effect GLS regression were used to describe and analyze the data.Result - The study found that, ownership structure (ownership concentration and management shareholding) has significant negative effect on loan quality of banks in Nigeria.Implication - The implications of this research is that increased ownership concentration as well as management shareholding can strengthen banks’ loan quality owing to reduced proportion of depositors funds used to finance loan. This could spur confidence in the bank by the general public with regards to the safety of their deposits.Originality - This study is different from other studies that concentrated on the use of ownership structure in relations to various financial performance measurements such as ROA, ROE, NPM among other. In this study, effort was made to consider the financial health of banks owing to the nature of their business (loan).